Repairing short shot defects in vulcanized rubber: A study on mechanical performance after compound addition - David Juan Antonio Filemon Silitonga; Muh. Wahyu Sya'bani (Politeknik ATK Yogyakarta, 2025)
The rubber industry plays a crucial role in global manufacturing, with Indonesia being one of the leading natural rubber producers. One of the major processing defects encountered in rubber moulding is insufficient material loading, also known as a short shot, which can result in significant material waste and product rejection. This study investigates a repair method that involves adding a fresh rubber compound to patch defective rubber specimens. The method was applied by trimming a portion of the vulcanized rubber and replacing it with a fresh compound of the same formulation, followed by re-vulcanization. Mechanical properties, including tensile strength, elongation at break, tear resistance, hardness, and abrasion resistance, were evaluated following ASTM standards. Results indicated that repaired specimens generally retained acceptable mechanical performance, with abrasion resistance improving alongside increased patching percentages. These findings suggest that patching short-shot defects with fresh compound is a promising and cost-effective approach for reducing waste while maintaining product quality.